2019
DOI: 10.4085/1062-6050-349-18
|View full text |Cite
|
Sign up to set email alerts
|

Sport Specialization and Increased Injury Frequency in Youth Baseball Players: A Prospective Study

Abstract: Context Sport specialization is thought to be a primary contributor to the throwing-related injury risk in youth baseball players. Objective To (1) establish arm-injury incidence in a cohort of male youth (9–12 years old) baseball players and (2) examine sport specialization and the frequency of arm injuries in the same cohort. Design Cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
0
24
1
Order By: Relevance
“…Both findings are behaviors commonly reported by highly specialized athletes that have been linked with injury. 3,11,36 This relationship with injury, however, was not found in the present study. 14,25,30 The second key finding of this study was that specialization was associated with worse throwing arm health.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Both findings are behaviors commonly reported by highly specialized athletes that have been linked with injury. 3,11,36 This relationship with injury, however, was not found in the present study. 14,25,30 The second key finding of this study was that specialization was associated with worse throwing arm health.…”
Section: Discussioncontrasting
confidence: 71%
“…Our results are in agreement with the many studies that have identified sport specialization as a risk factor for overuse injury among large cohorts of athletes from multiple sports 4,12,14,18,27,28,30 and also with the few studies that have specifically examined baseball players. 3,11,35 Arnold et al 3 prospectively followed youth baseball players, aged 9 to 12 years, who self-classified as specialized or nonspecialized and found that the frequency of arm injuries was greater among specialized players compared with nonspecialized players. 3 Similarly, sport specialization was associated with previous upper extremity overuse injury history and lower YTS score in a sample of 551 high school baseball players.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In a recent study of youth baseball players younger than 13 years, 83% of players met the study's criteria to be considered specialized in baseball, and those who were specialized reported a higher frequency of throwing-related arm injuries compared with players who were not specialized. 2 Similarly, in another recent study of high school baseball players, 52% of players met the study's criteria of being highly specialized, and those who were highly specialized reported greater rates of upper extremity overuse injuries in the previous year and poorer subjective throwing arm function. 14 Evidence suggests that adolescent baseball specialization may be associated with short-term negative effects on upper extremity health during players' adolescent baseball careers 2,14 ; however, the long-term effects of early baseball specialization on upper extremity health are not well-understood.…”
mentioning
confidence: 94%
“…13 Sport specialization, defined as year-round intensive training in a single sport while excluding other sports, 7 is a popular trend among youth baseball players. 2 The high-volume training, repetitive tissue stresses, and limited rest associated with sports specialization could play a role in the high rates of noncontact and overuse upper extremity injuries we have observed in college baseball players. A recent meta-analysis suggests that high and moderate sport specialization during adolescence is associated with a greater risk for overuse injury across diverse sports.…”
mentioning
confidence: 95%